The challenges of managing digital business maturity in the technological gap - I. S. Prokhorova; A. V. Elkhova (Вестник университета)
The article examines the current state of the Russian economy, which is at the active growth stage of the fifth technological order, and the related problems of managing digital maturity and digital business transformation. The existing technological gap between the Russian and global economies has a direct impact on the level of digital technology diffusion among representatives of all sectors of the economy and slows down the process of digital transformation, hindering the transition to a digital economy. The study subject is the management of business digital maturity in the current technical, technological and economic conditions. The study purpose is to identify the constraining factors of the digital transformation of Russian business in the conditions of technological lag. Empirical, logical, and comparative methods were used in the study. The scientific novelty of the research results consists in the problem consideration of the impact of technological lag of the IT sector on the management of business digital transformation in the new geopolitical conditions.